2018
DOI: 10.1007/s00268-018-4574-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism is Underdiagnosed and Suboptimally Treated in the Clinical Setting

Abstract: PurposeTo evaluate whether patients presenting with laboratory results consistent with primary hyperparathyroidism (pHPT) are managed in accordance with guidelines.MethodsThe laboratory database at a hospital in Sweden, serving 127,000 inhabitants, was searched for patients with biochemically determined pHPT. During 2014, a total of 365 patients with biochemical laboratory tests consistent with pHPT were identified. Patients with possible differential diagnoses or other reasons for not being investigated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…These findings replicate and expand upon earlier research demonstrating that 63% of hypercalcemic patients with nephrolithiasis have PTH levels measured and 47-71% of patients with a diagnosis of PHP are not referred for surgical evaluation. 2,16,17 If the rate of 1.94% of hypercalcemia is extrapolated to this entire cohort of patients, then of the 348 patients who did not have serum calcium measured it can be estimated that seven people had missed hypercalcemia. Based on the 100% rate of elevated or non-suppressed PTH for patients in our cohort with hypercalcemia, presuming the four hypercalcemia patients that did not have PTH checked did have PHP and the additional three patients with PHP who did not have surgical or specialty referral, we estimate that 14 patients or 1.4% of our cohort did not have appropriate definitive management of PHP with parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings replicate and expand upon earlier research demonstrating that 63% of hypercalcemic patients with nephrolithiasis have PTH levels measured and 47-71% of patients with a diagnosis of PHP are not referred for surgical evaluation. 2,16,17 If the rate of 1.94% of hypercalcemia is extrapolated to this entire cohort of patients, then of the 348 patients who did not have serum calcium measured it can be estimated that seven people had missed hypercalcemia. Based on the 100% rate of elevated or non-suppressed PTH for patients in our cohort with hypercalcemia, presuming the four hypercalcemia patients that did not have PTH checked did have PHP and the additional three patients with PHP who did not have surgical or specialty referral, we estimate that 14 patients or 1.4% of our cohort did not have appropriate definitive management of PHP with parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this population-based case-control study, all patients operated on with PTX for PHPT in Sweden, between 1 January 2008 and 31 December 2017, were identified and included by use of Swedish personal identity numbers through The Scandinavian Register for Thyroid, Parathyroid, and Adrenal Surgery (SQRTPA) and the Swedish National Cancer Register (SCR). SQRTPA was started in 2004 and is a well validated nationwide Swedish quality register for endocrine surgical procedures 17 . SQRTPA includes information on patients with PTX, including the date of diagnosis and PTX, preoperative calcium levels (mmol/l) and adenoma weights (g).…”
Section: Methodsmentioning
confidence: 99%
“…Large differences in the management of PHPT in countries with universal healthcare similar to Sweden are reported 12–14 as well as underutilization of PTX in the elderly population 15 . Furthermore, regional differences in healthcare utilization in Sweden are of a considerable magnitude and largely unexplained by supply and demand 16 , 17 . The management of the Swedish healthcare system is decentralized to the country’s 21 semi-autonomous regions, which are regulated by the Health and Medical Services Act (2017:30).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies [13][14][15][16][17][18][19] have reported the underdiagnosis and undertreatment of PHP. Because the disease is often asymptomatic, 30 whether it had a clinically meaningful impact on patients was unknown.…”
Section: Jama Network Open | Otolaryngologymentioning
confidence: 99%
“…12 Because many patients are asymptomatic and PHP is incidentally discovered, the diagnosis is frequently not actively pursued to identify candidates for surgery. [13][14][15][16][17][18][19] In this cohort study, we sought to use the largest sample size to date from health care organizations (HCOs) across the US to determine the outcomes associated with missed diagnoses, increased time to diagnosis, and treatment delay on patients. We hypothesized that all would be associated with increased symptoms and diagnoses associated with PHP.…”
Section: Introductionmentioning
confidence: 99%